Instability of connected oscillator system under action of multiplicative fluctuations - Buts, V.A.; Kovalchuk, I.K. (Вопросы атомной науки и техники, 2003)
Studying of many oscillatory and wave processes is reduced to the studying of dynamics of connected oscillators. Parameters of these oscillators may be under influence fluctuation forces. Instability in this case develops. Such instability can be named fluctuation parametrical instability. In systems with one degree of freedom (one oscillator) this instability is investigated. Increment of it is proportional to intensity of fluctuations. In the present work it is shown, that in systems with the big number degree of freedom (two, three connected oscillators) may be realized conditions when such increment essentially grows. Possible consequence of such increase of increment may be fast diffusion fluctuations in systems with the big number degree of freedom.